$\newcommand{\B}[1]{{\bf #1}} \newcommand{\R}[1]{{\rm #1}}$
 from pycppad import * # Example using a_float ------------------------------------------------------ def pycppad_test_reverse_1(): # start record a_float operations x = numpy.array( [ 2. , 3. ] ) # value of independent variables a_x = independent(x) # declare a_float independent variables # stop recording and store operations in the function object f a_y = numpy.array( [ 2. * a_x[0] * a_x[1] ] ) # dependent variables f = adfun(a_x, a_y) # f(x0, x1) = 2 * x0 * x1 # evaluate the function at a different argument value p = 0 # order zero for function values x = numpy.array( [ 3. , 4. ] ) # argument value fp = f.forward(p, x) # function value assert fp[0] == 2. * x[0] * x[1] # f(x0, x1) = 2 * x0 * x1 # evalute derivative of f(x0, x1) p = 1 # order one for first derivatives w = numpy.array( [ 1. ] ) # weight in range space fp = f.reverse(p, w) # derivaitive of weighted function assert fp[0] == 2. * x[1] # f_x0 (x0, x1) = 2 * x1 assert fp[1] == 2. * x[0] # f_x1 (x0, x1) = 2 * x0 # Example using a2float ------------------------------------------------------ def pycppad_test_reverse_1_a2(): # start record a_float operations a_x = ad(numpy.array( [ 2. , 3. ] )) # value of independent variables a2x = independent(a_x) # declare a2float independent variables # stop recording and store operations in the function object f a2y = numpy.array( [ 2. * a2x[0] * a2x[1] ] ) # dependent variables a_f = adfun(a2x, a2y) # f(x0, x1) = 2 * x0 * x1 # evaluate the function at a different argument value p = 0 # order zero for function values a_x = ad(numpy.array( [ 3. , 4. ] )) # argument value a_fp = a_f.forward(p, a_x) # function value assert a_fp[0] == 2. * a_x[0] * a_x[1] # f(x0, x1) = 2 * x0 * x1 # evalute derivative of f(x0, x1) p = 1 # order one for first derivatives a_w = ad(numpy.array( [ 1. ] )) # weight in range space a_fp = a_f.reverse(p, a_w) # derivaitive of weighted function assert a_fp[0] == 2. * a_x[1] # f_x0 (x0, x1) = 2 * x1 assert a_fp[1] == 2. * a_x[0] # f_x1 (x0, x1) = 2 * x0